2015
DOI: 10.1111/jvim.12521
|View full text |Cite
|
Sign up to set email alerts
|

Canine Pancreatic‐Specific Lipase Concentrations in Dogs with Heart Failure and Chronic Mitral Valvular Insufficiency

Abstract: BackgroundChronic mitral valvular insufficiency (CMVI) in dogs is very common and might cause clinical signs of congestion and poor tissue perfusion.HypothesisPoor tissue perfusion from CMVI causes pancreatitis in dogs, as indicated by serum pancreatic lipase concentrations.AnimalsSixty‐two client‐owned dogs consisting of 40 dogs with different stages of heart failure from CMVI and 22 age‐matched healthy dogs, based on full cardiac exam and routine laboratory tests.MethodsProspective, controlled, observational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…Therefore, the authors recommend that a quantitative pancreatic lipase assay should be performed in addition to an AUS in all dogs being assessed for pancreatitis. One potential explanation for the lower correlation between UPASS and Spec cPL than between UPASS and CDx is that primary nonpancreatic diseases and steroid treatment have been associated with an above reference interval Spec cPL concentration, although the clinical relevance of these increases are often unknown …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the authors recommend that a quantitative pancreatic lipase assay should be performed in addition to an AUS in all dogs being assessed for pancreatitis. One potential explanation for the lower correlation between UPASS and Spec cPL than between UPASS and CDx is that primary nonpancreatic diseases and steroid treatment have been associated with an above reference interval Spec cPL concentration, although the clinical relevance of these increases are often unknown …”
Section: Discussionmentioning
confidence: 99%
“…explanation for the lower correlation between UPASS and Spec cPL than between UPASS and CDx is that primary nonpancreatic diseases and steroid treatment have been associated with an above reference interval Spec cPL concentration, although the clinical relevance of these increases are often unknown. 21,[26][27][28][29][30][31][32] When evaluating individual components of the UPASS, this study . This is likely due to the fact that diseases other than pancreatitis cause pancreatic edema, including hypoalbuminemia and portal hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Also, close correlation of serum cPLI concentration was found in the left atrial to aorta (LA/Ao) ratio (r = 0.597; P = 0.000) and the severity of heart failure (r = 0.530; P = 0.000). This study found that the CMVI is associated with pancreatic injury in congestive heart failure due to the CMVI [27].…”
Section: Laboratory Testsmentioning
confidence: 54%
“…Poor tissue perfusion from CMVI causes pancreatitis in dogs, as indicated by serum pancreatic lipase concentrations. One recent study has evaluated the prevalence of pancreatitis in 62 client-owned dogs consisting of 40 dogs with different stages of heart failure from CMVI and 22 age-matched healthy dogs [27]. Serum canine pancreatic lipase immunoreactivity (cPLI) concentrations were determined by quantitative cPLI test in healthy and CMVI groups in this study.…”
Section: Laboratory Testsmentioning
confidence: 99%
See 1 more Smart Citation